TRAF6-NF-κB pathway is essential for interleukin-1-induced TLR2 expression and its functional response to TLR2 ligand in murine hepatocytes - Matsumura, Takayuki (Blackwell Science Inc, 2003)
We have previously reported that the expressions of TLR2 and TLR4 mRNA are differentially regulated in mouse liver and in the parenchymal cells. In the present study, we investigated the mechanism of the up-regulatory effects of interleukin-1α (IL-1α), tumour necrosis factor-α (TNF-α), lipopolysaccharide (LPS), or bacterial lipoprotein (BLP) on TLR2 mRNA expression in primary cultured murine hepatocytes. Although TLR2 mRNA stability was not affected, these treatments enhanced NF-κB activity and TLR2 gene transcription simultaneously. The up-regulation of TLR2 transcription in response to these reagents was completely inhibited by blocking the NF-κB activation pathway, demonstrating a pivotal role of NF-κB activation in the regulation of hepatocyte TLR2 transcription. The expression of TLR2 protein by hepatocytes was also remarkably up-regulated by IL-1α and, to a lesser extent, by TNF-α as well, but not by LPS or BLP. In addition, pretreatment of mice with IL-1α markedly increased the BLP (a ligand for TLR2)-induced serum level of serum amyloid A (SAA), an acute-phase protein predominantly produced by hepatocytes, indicating that IL-1α may also up-regulate functional TLR2 in vivo. These results demonstrate that IL-1α, through activating the TRAF6-NF-κB pathway, serves as the most potent inducer for TLR2 up-regulation, and plays an important role in the regulation of hepatocyte functions by augmenting the hepatocyte response to bacteria or bacterial products.